Anchoring of palladium nanoparticles on N-doped mesoporous carbon. Issue 37 (16th September 2020) - Warczinski, Lisa; Hu, Bin; Eckhard, Till; Peng, Baoxiang; Muhler, Martin; Hättig, Christof
Abstract : Pyridinic nitrogen atoms are preferential adsorption sites for palladium nanoparticles and lead to a change of the Pd oxidation state from Pd 0 to Pd 2+ . Abstract : Pd nanoparticles deposited on nitrogen-doped mesoporous carbon are promising catalysts for highly selective and effective catalytic hydrogenation reactions. To design and utilize these novel catalysts, it is essential to understand the effect of N doping on the metal–support interactions. A combined experimental (X-ray photoelectron spectroscopy) and computational (density functional theory) approach is used to identify preferential adsorption sites and to give detailed explanations of the corresponding metal–support interactions. Pyridinic N atoms turned out to be the preferential adsorption sites for Pd nanoparticles on nitrogen-doped mesoporous carbon, interacting through their lone pairs (LPs) with the Pd atoms via N-LP – Pd dσ and N-LP – Pd s and Pd dπ – π* charge transfer, which leads to a change in the Pd oxidation state. Our results evidence the existence of bifunctional palladium nanoparticles containing Pd 0 and Pd 2+ centers.